Education, Business Capital, Marketing Access, and Location as Determinants of MSME Success in Bengkulu City - Rudi Hartono; Azuwandri (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
Micro, small, and medium enterprises (MSMEs) play an important role in employment creation and regional economic activity, yet their success is shaped by managerial and market-related conditions. This study examines the effects of education, business capital, marketing access, and business location on MSME success in Bengkulu City. A quantitative cross-sectional design was applied using primary data collected through a five-point Likert-scale questionnaire. The population consisted of 44,627 MSMEs, from which 100 respondents were selected through probability sampling. After outlier removal, 93 observations were analyzed using multiple linear regression in SPSS 23. The measurement items were valid and reliable, and the regression model met the assumptions of normality, multicollinearity, and heteroscedasticity. Education had a positive and significant effect on MSME success (B = 0.092; p = 0.003), as did marketing access (B = 0.136; p < 0.001) and business location (B = 0.090; p = 0.002). Business capital did not have a statistically significant effect (B = -0.036; p = 0.246). Collectively, the four predictors significantly explained MSME success, F(4, 88) = 37.709, p < 0.001, with R2 = 0.632 and adjusted R2 = 0.615. The findings indicate that human capital, market reach, and strategic location are more consistent determinants of MSME success than the amount of financial capital alone. Capacity-building programs should therefore combine managerial education, digital marketing assistance, and evidence-based location planning with access to finance.